The Influence of Video Direct Instruction Model to Folklore Listening Skills in Elementary Schooll - Sabri, Tahmid; Soeharto, Soeharto; Afrizan, Afrizan (Bina Nusantara University, 2020)
The research aimed to analyze the effect of the direct instruction model assisted by audio media on listening skills. The experimental method was used using a quasi-experimental design. Participants were a fifth-grade students in the elementary school at Pontianak. Data collected used paper-based tests in the form of multiple-choice tests. The results show that the average posttest for the experimental group is 77,08. The average posttest for the control group is 70,96. T-test results are 2,217 and t-table α = 5% (with dk = 24 + 26 - 2 = 48) of 1,678, so t-count (2,217)> t-table (1,678). Therefore, it can be concluded that there is an influence of the audio learning model-assisted directly by audio media on listening skills on folklore. Besides that, the direct instruction model assisted by audio media has a good influence on listening skills, especially for fifth-grade students.